EFEKTIFITAS SUPERPLASTICIZER PADA BETON BERBASIS LIMBAH SAWIT TERHADAP SIFAT MEKANIS DAN SIFAT FISIK BETON - Muhammad Gala Garcya; Juli Ardita Pribadi; Boby Rahman (Politeknik Negeri Bengkalis, 2023)
Spent Bleaching Earth (SBE) is one of the problems that triggers soil damage due to its fairly common use but minimal utilization of this waste. SBE is waste resulting from Crude Palm Oil (CPO) filtering. CPO during initial processing has a color that tends to be dark, so it requires bleaching powder (Fresh Spent Bleaching Earth) to filter the oil. The remainder of this filtering is known as SBE. If this waste is allowed to accumulate for too long, it has the potential to cause damage to the soil and the surrounding environment, even land fires due to the oil content in it. Therefore, in the form of utilizing and reducing environmentally damaging waste, innovation is needed, such as using this waste into the concrete mix. The process of making this concrete will be the same as concrete in general but using a different mix so that this waste can be optimally utilized. Based on the test results obtained, SBE has the potential to be one of the recommendations for concrete mixtures that are applied to seawater because the compressive strength increases as the concrete ages by 36.2% at 28 days. Whereas in fresh water the compressive strength value tends to decrease by 15.9%. So based on testing, SBE is more suitable for use in seawater environments than freshwater. Keywords: Waste Concrete, Compressive Strength, Palm Processed Oil, Spent Bleaching Earth